An Incidental Finding of Gastric Mucosa-Associated Lymphoma (MALToma) in a Sleeve Gastrectomy with Literature Review - Brenda Mai; Michaelangelo Friscia; Pamela Younes; Jaiyeola Thomas-Ogunniyi; Lei Chen (Case Reports in Hematology)
Mucosal-associated lymphoid tissue (MALT) lymphoma can typically be identified as a mass lesion or nodularity endoscopically and macroscopically. We report an incidental finding of a Helicobacter pylori gastric mucosal-associated lymphoid tissue (MALT) lymphoma in a sleeve gastrectomy specimen with no gross examination findings.